IMPLEMENTASI KEBIJAKAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) STUDI KASUS DI KECAMATAN DENPASAR UTARA PROVINSI BALI - Monica, Vocci; Noak, Piers Andreas; Winaya, I Ketut (CITIZEN CHARTER, 2015)
ABSTRACT Implementation of the regulations of Law No. 24 of 2013 on the Amendment of Law No. 23 Year 2006 concerning Population Administration has been implemented in Denpasar, in particular in North Denpasar District. However, after the handover of authority from the central government to local governments beginning of 2015, there are still obstacles in the implementation of e-ID card at the Department of Population and Civil Registration and record personal data in Denpasar District Office North. Problems that occur due to the limited number of forms provided by the Ministry of the Interior to the Department of Population and Civil Registration Denpasar, so far the implementation of e-ID in the Denpasar District North unresolved. This policy is expected to realize the implementation of the e-ID card program in North Denpasar District optimally. The methodology used in this research is descriptive qualitative research method. To obtain the data, researchers conducted observations of spaciousness to see the phenomenon of direct and conduct interviews to sources associated with the implementation of e-ID card policy at Denpasar District North. The conclusion of this study are the factors which resulted in the completion of e-ID in the Denpasar District North, caused by communication, resources, disposition and bureaucratic structures that are not running optimally. Â Keywords : Implementation , Electronic Identity Card (e-ID)